2011
DOI: 10.1590/s1984-29612011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological detection of Leishmania spp. in captive wild animals from Ilha Solteira, SP, Brazil

Abstract: Leishmaniasis is a zoonotic disease that affects 12 million people worldwide. Several mammalian species can serve as a reservoir for this disease. Dogs are the main reservoir for visceral leishmaniasis in urban areas, which has become a serious public health concern in Brazil. The aim of this study was to evaluate the presence of Leishmania spp. in captive wild animals from Ilha Solteira, São Paulo, Brazil. Blood and various tissues samples were collected from animals of five different species: Speotho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
10
0
6
Order By: Relevance
“…In our findings, three animals had anti-Leishmania spp. antibodies, which is consistent with other studies (CURI et al, 2006;JUSI et al, 2011) Trypanosomatidae family cannot to be ruled out, as has been suggested by some authors (LUCIANO et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In our findings, three animals had anti-Leishmania spp. antibodies, which is consistent with other studies (CURI et al, 2006;JUSI et al, 2011) Trypanosomatidae family cannot to be ruled out, as has been suggested by some authors (LUCIANO et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Estudos recentes confirmaram também a presença de Leishmania sp. em lobo-guará -Cerdocyon brachyurus e cachorro-vinagre -Speothos venaticus mantidos em conservação ex situ (Courtenay et al 1996, Maurício et al 1999, Brasil 2005, Luppi et al 2008, Lima et al 2009, Souza et al 2010, De Almeida et al 2011, Jusi et al 2011.…”
Section: Introductionunclassified
“…A utilização de conjugados à base de imunoglobulinas anti-IgG de cão doméstico ligadas a enzimas como a peroxidase é descrita para a pesquisa de anticorpos anti-Leishmania sp. em ensaios imunoenzimáti-cos para C. thous (Courtenay et al 2002), S. venaticus (Jusi et al 2011), Vulpes vulpes (Mancianti, Mignone & Galestri 1994) e C. brachyurus (Curi, Miranda & Talamoni 2006). Tal utilização baseia-se na propriedade de ligação cruzada, devido à semelhança genética entre indivíduos pertencentes à mesma família.…”
Section: Introductionunclassified
“…domesticated animal participants. The transmission of the parasite is typically associated with environmental degradation, which forces vector adaptation from wild to urban areas-this facilitates human infection (Jusi et al, 2011). In Northeastern Brazil, this disease is endemic and its incidence is increasing (Dantas-Torres and Brandao-Filho, 2006;Marcondes and Rossi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the innate response of naïve PMBCs in dogs to Leishmania may contribute to the current understanding of the early cellular events triggered by parasite infection (Rodrigues et al, 2009). Studies have confirmed the seropositivity of crab-eating foxes (Cerdocyon thous), but these animals are rarely infectious or symptomatic (Luppi et al, 2008;Souza et al, 2010;Jusi et al, 2011;Richini-Pereira et al, 2014) despite reports of individuals with clinical signs quickly recovering (Courtenay et al, 2002).…”
Section: Introductionmentioning
confidence: 99%